2019
DOI: 10.31734/agronomy2019.01.112
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nutrition optimization on the productivity of spring oil crops on the southern chernozem in the zone of Ukrainian steppe under the influence of biopreparations

Abstract: Гамаюнова В., Хоненко Л., Москва І., Кудріна В., Глушко Т. Вплив оптимізації живлення на продуктивність ярих олійних культур на чорноземі південному в зоні Степу України під впливом біопрепаратів Представлено матеріали досліджень, проведених на чорноземі південному з ярими олійними культурами впродовж 2014-2018 рр., з порівняльною характеристикою їх щодо врожаю та основних показників якості насіння. Наведено рівні врожайності насіння ярих олійних культур, які вирощують в умовах Південного Степу Українисоняшник… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…m 2 /ha. Other researchers ( Gamayunova et al, 2019;Melnyk et al, 2020) found that for varieties and hybrids of the intensive type, which currently prevail in agricultural production, the optimal leaf area is within 50-60 thous. m 2 / ha.…”
Section: Figure 3 the Proportion Of Influence Of The Factors Under St...mentioning
confidence: 97%
“…m 2 /ha. Other researchers ( Gamayunova et al, 2019;Melnyk et al, 2020) found that for varieties and hybrids of the intensive type, which currently prevail in agricultural production, the optimal leaf area is within 50-60 thous. m 2 / ha.…”
Section: Figure 3 the Proportion Of Influence Of The Factors Under St...mentioning
confidence: 97%
“…Соняшник є культурою дуже вимогливою до кліматичних умов, потребує значної кількості вологи і сонячної енергії в певному співвідношенні в різні періоди вегетації, яка, залежно від групи стиглості, триває від 80 до 130 діб. У питанні впровадження нових, економічно вигідних технологій у рослинництво, на особливу увагу заслуговує такий елемент вирощування, як позакореневе підживлення посівів сільськогосподарських рослин мікроелементами та рістрегулюючими речовинами (Gamayunova et al, 2019c). За кореневого живлення рослини поглинають із ґрунтового розчину понад 70 різних хімічних елементів, забезпечуючи себе переважно трьома основними макроелементами -азотом, фосфором і калієм.…”
Section: вступunclassified
“…Optimising the supply of nutrients during the growing season of crops results in more efficient use of moisture, regardless of the conditions prevailing during the growing years (Pinkovsky et al, 2019). This was determined during research with various crops, including sunflower (Domaratskiy et al, 2019;Gamayunova et al, 2019). Data obtained by scientific institutions indicate that sunflower should occupy no more than 20% of the crop rotation structure (Tkalich et al, 2018).…”
Section: Introductionmentioning
confidence: 99%